An investigation of orotic acid levels in the breastmilk of smoking and non-smoking mothers - Karatas, F (Springernature, 2002)
Aim: In this study; orotic acid levels in the milk of smoking and non-smoking mothers were investigated by high-performance liquid chromatography (HPLC). Results: It was found that the amount of orotic acid in the milk of smoking mothers (3.92 +/- 0.20 mug/ml) was higher than that of non-smoking mothers (1.66 +/- 0.15 mug/ml). Orotic acids levels in the milk of smoking mothers in comparison with non-smokers were found to be statistically significant (P < 0.005). Conclusion: Smoking may have increased the orotic acid levels by affecting pyrimidine biosynthesis pathway.
Keywords: breastmilk; orotic acid; smoking; HPLC